A novel medium-entropy (TiVNb)2AlC MAX phase: Fabrication, microstructure, and properties. (20th February 2023) - He, Guangqi; Zhang, Yi; Yao, Pei; Li, Xingchao; Ma, Ke; Zuo, Jun; Li, Meishuan; Liu, Changsheng; Xu, Jingjun
Highlights: The medium-entropy MAX phase ceramic was fabricated for the first time. Nearly pure medium-entropy (TiVNb)2 AlC was prepared by hot pressing. (TiVNb)2 AlC exhibits lower thermal conductivity compared to the individual MAX phases. Young's modulus, Vickers hardness, and bending strength were reported. Abstract: Medium- or high-entropy materials have great potential for applications due to their diverse compositions and unexpected physicochemical properties. Herein, a novel medium-entropy (TiVNb)2 AlC was synthesized via hot pressing at 1400 °C from three individual M2 AlC (M=Ti, V, Nb) MAX phases. The microstructure of (TiVNb)2 AlC was characterized from the microscale to the atomic scale by scanning electron microscope microscopy (SEM), scanning transmission electron microscopy (STEM), and energy dispersive spectroscopy (EDS). The results showed that Ti, V, and Nb atoms were fully solid-soluble in the M-sites of the M2 AlC MAX phase. Compared with three individual MAX phases, the thermal conductivity of (TiVNb)2 AlC was reduced greatly in the temperature range of 293–1473 K, and its mechanical properties (including Young's modulus, Vickers hardness, and bending strength) were all increased due to the solid solution strengthening and electronic mechanism. Graphical abstract: Image, graphical abstract